PENGARUH MODEL TREFFINGER BERBANTUAN WEB LIVEWORKSHEET TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI UPTD SMP NEGERI 1 KISARAN - Nova Eliza Silaen; Dewi Astuti (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The aim of this research is to determine the effect of the Treffinger model assisted by a web live worksheet on the mathematical problem solving abilities of class VIII UPTD students at SMP Negeri 1 Kisaran for the 2023/2024 academic year. This research is experimental research with a Pretest-Posttest Control Group Design research design. The population in this study were all class VIII students at UPTD SMP Negeri 1 Kisaran. Two classes were selected using purposive sampling to be used as research samples. Class VIII-1 as an experimental class is taught using the Treffinger model with the help of a web live worksheet, while class VIII-2 is a control class taught using a direct learning model. The data obtained in this research were in the form of students' mathematical problem solving ability scores which were analyzed using the t-test. Based on the data obtained on students' mathematical problem solving abilities, it is known that the average value of experimental class students' mathematical problem solving abilities is 83.67, which is greater than that of the control class, 73.67. From the results of the hypothesis test calculations, it is obtained that t_count>t_table is 4.94 > 1.67, so H_0 is rejected and H_1 is accepted. Based on the results of data analysis, it was found that there was an influence of the Treffinger model assisted by web live worksheet on students' mathematical problem solving abilities at UPTD SMP Negeri 1 Kisaran. Keywords: Treffinger Model; Web Liveworksheet; Mathematical Problem Solving Ability Abstrak: Tujuan penelitian ini  adalah untuk mengetahui pengaruh model Treffinger berbantuan web liveworksheet terhadap kemampuan pemecahan masalah matematis siswa  kelas VIII UPTD SMP Negeri 1 Kisaran tahun ajaran 2023/2024. Penelitian ini merupakan penelitian eksperimen dengan desain penelitian Pretest-Posttest Control Group Design. Populasi dalam penelitian ini adalah seluruh siswa kelas  VIII di UPTD SMP Negeri 1 Kisaran. Dua kelas dipilih secara purposive sampling untuk dijadikan sampel penelitian. Kelas VIII-1 sebagai kelas eksperimen yang diajarkan dengan menerapkan model Treffinger berbantuan web liveworksheet sedangkan kelas VIII-2 kelas kontrol diajarkan dengan model pembelajaran langsung. Data yang diperoleh dalam penelitian ini berupa skor kemampuan pemecahan masalah matematis siswa yang dianalisis dengan uji-t. Berdasarkan data kemampuan pemecahan masalah matematis siswa yang telah diperoleh, diketahui bahwa rata-rata nilai kemampuan pemecahan masalah matematis siswa kelas eksperimen sebesar 83,67 lebih besar dari kelas kontrol 73,67. Dari hasil perhitungan uji hipotesis diperoleh t_hitung>t_tabel yaitu  sebesar 4,94 > 1,67 maka H_0 ditolak dan H_1 diterima. Berdasarkan hasil analisis data diperoleh bahwa ada pengaruh model  Treffinger berbantuan web liveworksheet terhadap kemampuan pemecahan masalah matematis siswa di UPTD SMP Negeri 1 Kisaran. Kata kunci: Model Treffinger; Web Liveworksheet; Kemampuan Pemecahan Masalah Matematis